Whey conversion scenarios for sustainable lactic acid, ethanol and hydrogen production: techno-economic aspects of biofuels and biochemical production - Ozturk, Abdullah Bilal; Acar, Zeynep Deniz; Yilmaz, Fuat; Sagdic, Osman (WILEY, 2025)
Growing environmental concerns and a movement toward sustainable greenhouse gas mitigation strategies have driven research into alternative resources. Whey, a major byproduct of the cheese industry, is produced globally at approximately 180 million tons per year. It is important to recycle this waste effectively through the circular economy (CE) and sustainable bioprocess strategies. However, its commercial viability must be validated through technical and economic analyses, such as techno-economic assessment (TEA), to support Sustainable Development Goals (SDGs), particularly affordable and clean energy (SDG 7) and climate action (SDG 13). This study examines whey valorization through three biochemical pathways: (1) lactic acid production via lactic acid bacteria (LAB) fermentation, (2) ethanol production through anaerobic fermentation, and (3) hydrogen production using dark and photo fermentation. Profitability assessments indicate that lactic acid and hydrogen production are the most promising, demonstrating a higher net present value (NPV), internal rate of return (IRR), gross margin (GM), and return on investment (ROI), and shorter payback period (PBP). Specifically, lactic acid production, based on processing 500,000 L of whey daily over a 20-year project lifespan at a 5% discount rate, resulted in an NPV of $191 million, an IRR of 12.9%, a PBP of 5.2 years, and an ROI of 16.6%.
Keywords: whey; lactic acid; ethanol; hydrogen; techno-economic assessment; ENVIRONMENTAL-IMPACT ASSESSMENT; CHEESE WHEY; BIOHYDROGEN PRODUCTION; BIOETHANOL PRODUCTION; ECONOMIC-EVALUATION; MICROBIAL COMMUNITY; WASTE VALORISATION; DARK FERMENTATION; FOOD; RESIDUES; Biotechnology & Applied Microbiology; Energy & Fuels